2009
DOI: 10.1007/s00449-009-0363-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of lipase-catalyzed glucose ester synthesis in ionic liquids

Abstract: Lipase-catalyzed esterification of glucose with fatty acids in ionic liquids (ILs) mixture was investigated by using supersaturated glucose solution. The effect of ILs mixture ratio, substrate ratio, lipase content, and temperature on the activity and stability of lipase was also studied. The highest yield of sugar ester was obtained in a mixture of 1-butyl-3-methylimidazolium trifluoromethanesulfonate ([Bmim][TfO]) and 1-methyl-3-octylimidazolium bis[(trifluoromethyl)-sulfonyl]amide ([Omim][Tf(2)N]) with a vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 18 publications
3
23
0
1
Order By: Relevance
“…The effect of reaction temperature on the v app and molecular weight in the Novozym 435 catalyzed synthesis of poly(1'‐ O ‐3‐hydroxyacyl‐sucrose) in chloroform‐DMSO ratio 4:1 (v/v) was observed (Table ). It has been previously stated that in micro‐aqueous sugar ester synthesis, the solubility and rate of sugar dissolution play an important role in product yield . In fact, in such reaction, the solubility of sugar moiety has been reported to largely rely on the reaction temperature and solvent polarity .…”
Section: Resultsmentioning
confidence: 99%
“…The effect of reaction temperature on the v app and molecular weight in the Novozym 435 catalyzed synthesis of poly(1'‐ O ‐3‐hydroxyacyl‐sucrose) in chloroform‐DMSO ratio 4:1 (v/v) was observed (Table ). It has been previously stated that in micro‐aqueous sugar ester synthesis, the solubility and rate of sugar dissolution play an important role in product yield . In fact, in such reaction, the solubility of sugar moiety has been reported to largely rely on the reaction temperature and solvent polarity .…”
Section: Resultsmentioning
confidence: 99%
“…ILs have also been used in the chemical synthesis of sugar esters . Moreover, many of them have been found to stabilize enzymes and consequently, ILs and mixtures of ILs and organic solvents have been successfully used in the enzymatic synthesis of different glucose esters .…”
Section: Introductionmentioning
confidence: 99%
“…As is known, the enzyme displays a high level of activity for sugar ester synthesis . However, it has been reported that the formation of carbamates by scCO 2 and the free amine groups on the surface of the enzyme can deactivate the enzyme .…”
Section: Resultsmentioning
confidence: 99%